Erythrocytes, a New Contributor to Age‐Associated Loss of Blood–Brain Barrier Integrity. Issue 20 (16th August 2021) - Amiri, Payam; DeCastro, Jonalyn; Littig, Joshua; Lu, Hsiang‐Wei; Liu, Chao; Conboy, Irina; Aran, Kiana
Abstract: Blood exchanges between young and old partners demonstrate old blood has a detrimental effect on brain health of young animals. Previous studies primarily investigate soluble blood factors, such as transforming growth factor‐beta, on the brain and the blood–brain barrier (BBB). However, the role of blood cellular components, particularly erythrocytes, has not been defined. Erythrocyte morphology and rigidity change as mammals age, altering their transport within the capillary bed. This impacts downstream biological events, such as the release of reactive oxygen species and hemoglobin, potentially compromising the BBB. Here, a micro electrical BBB (µE‐BBB), with cocultured endothelial and astrocytic cells, and a built‐in trans‐endothelial electrical resistance (TEER) system is described to monitor the effect of capillary shear stress on erythrocytes derived from young and old mice and people and the subsequent effects of these cells on BBB integrity. This is monitored by the passage of fluorescein isothiocyanate‐dextran and real‐time profiling of TEER across the BBB after old and young erythrocyte exposure. Compared to young erythrocytes, old erythrocytes induce an increased permeability by 42% and diminished TEER by 2.9% of the µE‐BBB. These results suggest that changes in circulating erythrocytes are a biomarker of aging in the context of BBB integrity. Abstract : The blood–brain barrier (BBB) is a vital structure that protects the brain from inhibitory molecules found in circulation. However, this barrier has been shown to become leaky with age. This study finds that erythrocytes derived from old mammals (mice and people) have deleterious effects on the integrity of the BBB, when compared to the young cells.